A simple approach to atom probe sample preparation by using shadow masks - Felfer, Peter; Mccarroll, Ingrid; Macauley, Chandra; Cairney, Julie M. (Ultramicroscopy, 2016)
Here, we present a new method that utilises shadow masks in a broad ion beam system to prepare atom probe samples. It is particularly suited to non-conductors and materials with surface layers such as surface oxides, implanted layers or thin films. This new approach bypasses the focused ion beam (FIB) lift-out step, increasing the sample throughput, dramatically reducing the required FIB beam time and decreasing the complexity of sample preparation. (C) 2015 Elsevier By. All rights reserve
Keywords: Atom probe tomography; Sample preparation; Focused ion beam; Broad ion beam